The Digitalization of Public Administration in Romania Compared with Member States of the European Union - Pripoaie, Rodica; Schin, George (EuroEconomica, 2023)
This study explores an important issue regarding the state of digitization of public administration in Romania compared to its level at the European level. In this paper, we analyze the level of digitization of public administration services in Romania, which aims at improving the interaction between the state and citizens, in the sense of increasing the quality of the offered services following the dynamics of society. Also, digitization aims at simplifying citizens’ lives, facilitating the interaction between them and public administration institutions, but also increasing citizens’ trust in the administration, which will ultimately lead to the economic development of communities and increase living standards. We have also analyzed the degree of digitization of Romania compared to other European states, a level reflected by a series of indicators used at the European level. We found that there is a direct link between the level of digitization and the development of a country. That is precisely why Romania should be concerned with accelerating the digitization process of public administration and reducing the existing gap in this field compared to other European states.